Bitter taste cells in the ventricular walls of the murine brain regulate glucose homeostasis - Qiang Yu; Igor Gamayun; Philipp Wartenberg; Qian Zhang; Sen Qiao; Soumya Kusumakshi; Sarah Candlish; Viktoria Götz; Shuping Wen; Debajyoti Das; Amanda Wyatt; Vanessa Wahl; et al. (Nature Communications, 2023)
The median eminence (ME) at the base of the brain controls body homeostasis. Here, the authors describe a functional tanycyte subpopulation at the ME which tastes the surrounding milieu, responds to metabolic signals and regulates glucose homeostasis.